REVIEW Rekayasa Genetika untuk Mengatasi Masalah-masalah Pascapanen - Darda Efendi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2005)
Flavr Savr tomato is a transgenic tomato which is transformed using Polyglacturonase gene in antisense orientation. This is the first whole food product of biotechnology that reachs the market, but unfortunately it does not succeed. Ethylene is thought to act as a natural triggering mechanism for fruit ripening and senescence. Lowering the production of endogenous ethylene from fruit should delay fruit ripening and senescence. Several ways to control ethylene biosynthesis are: inactivation of the gene encoding ACC synthase, ACC oxidase, metabolism of SAM so that ACC is not produced, or metabolism of ACC before it can be converted to ethylene. Effect of ethylene can also be blocked by blocking the perception of ethylene by specific tissues. Key words: Ethylene, ACC synthase, ACC oxidase, SAM hydrolase, genetic transformation.